The Effectiveness of Dumbbell Training on Volleyball Overhead Service Ability - Saman, Abdul; Asshagab, Muhtar; Marsuna; Angriawan, Tri (Performa, 2025)
The purpose of this study is to explore the effectiveness of dumbbell training on the ability to serve over the top of the volleyball game. The population in this study consisted of 30 students from SMA Negeri 6 Kendari. Sampling was done through a total sampling technique, which resulted in a sample of 30 people. The research instrument was the upper service ability test, the training method used was dumbbells. By applying statistical analysis, the t-test was carried out using SPSS version 25 software, it was revealed that there was a positive influence between arm muscle strength and upper service ability, with a value (t count) of 2.218 and a value that had a significant level of 0.000 <0.05. It was proven that there was a percentage increase of 20.05% in the pre-test and post-test after doing arm muscle strength training. These results mean the effectiveness of dumbbell training on the ability to serve over the top of the volleyball game.